“O povo clama” : um estudo dos discursos parlamentares acerca do sofrimento psíquico em adolescentes em conflito com a lei - Silva, Alana Katiúscia Schütz da (2021)
Since the creation of the Child and Adolescent’s Statute, numerous Law Projects have been created aiming at the application of Security Measures to those adolescents who have been diagnosed with some psychological suffering, and the increase of the term for institutionalization, so that such proposals never materialized. Thus, considering the debates inside the Chamber of Deputies about Security Measures for adolescents in conflict with the law, the present research sought to answer: how do the parliamentarians speeches think about the social control of adolescents in conflict with the law and suffering from psychological distress? The cut made is limited to the observations referring to the activity of the Chamber of Deputies in relation to the Child and Adolescent’s Statute between the years 2003 to 2020. The theoretical framework of the present work is Critical Criminology (in a broad sense). However, as this framework doesn’t bring specific methods of discourse, it was decided to work on the perspective of Critical Discourse Studies that help the researcher to detect indications about the social representations shared by the authors of the discourses. Furthermore, the present work was structured in two chapters. The first chapter aimed to highlight the social representations of the adolescent, with the evolution of legislation aimed at him from the Code of Minors of 1927, as well as to identify who is the adolescent punished in Brazil, bringing elements such as selectivity, race, poverty, socioeconomic issues. Also, demonstrate the criminal policy regarding adolescents in conflict with the law who suffer from psychological distress through the socio-educational measure of institutionalization, considered as the most serious constant in the current legislation. In addition, the chapter presents the correlation between the patient suffering from psychological distress and the adolescent and how compulsory hospitalization has been the resource used by the Judiciary to keep adolescent authors of infractions institutionalized. To this end, the second chapter shows the analysis of the speeches made by the parliamentarians regarding the proposals for the inclusion of Security Measures and/or their simulations related to adolescents in conflict with the law, divided into categories, analyzing how the Brazilian Legislative Power thinks about the social control of crime and criminal justice, and it is possible to identify how the speeches represent these adolescents. It was concluded that the elements contained in parliamentarians speeches about psychic suffering in adolescents in conflict with the law, whether in the justification of Draft Laws, in the explanations of reasons and in the opinions of the Commissions, make it possible to observe reproductions and perpetuations of speeches that nourish social inequality by not worrying about the recipients of their projects, which keeps these adolescents at the mercy of neglect and without an effective solution.